2018
DOI: 10.1177/2382120518757717
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Clinical-Year Medical Students: Factors Contributing to Effective Mentoring

Abstract: Theory:Academic mentoring is an effective method of enhancing undergraduate medical student academic performance, research productivity, career planning, and overall satisfaction.Hypotheses:This study investigates the relationship between mentor characteristics and mentee academic performance, with an emphasis on identifying students who need special support.Methods:A cross-sectional study was conducted among fourth-year medical students at King Abdulaziz University Faculty of Medicine undertaking the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
1
23
0
8
Order By: Relevance
“…Moreover, mentee engagement with mentoring can also pose a problem with a number of studies reporting low student participation 83,85. Similarly, a 2018 study of a mentorship program at King Abdulaziz University Faculty of Medicine, Saudi Arabia, reported that group meetings and one-on-one meetings were attended by only 60% and 49% of all students, respectively 87. The authors concluded that sustained mentor and administration staff motivation is prerequisite for a successful mentoring program.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, mentee engagement with mentoring can also pose a problem with a number of studies reporting low student participation 83,85. Similarly, a 2018 study of a mentorship program at King Abdulaziz University Faculty of Medicine, Saudi Arabia, reported that group meetings and one-on-one meetings were attended by only 60% and 49% of all students, respectively 87. The authors concluded that sustained mentor and administration staff motivation is prerequisite for a successful mentoring program.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of mentoring is as old as the nursing profession itself (Mariani 2012 :2; Olaolorunpo 2019 :142). Fallatah et al ( 2018 :1) defines mentoring as a unique relationship between experienced mentor offering guidance and support to an inexperienced mentee. Bynum ( 2015 :70) adds that mentoring occurs when the more knowledgeable person provides professional support to a less experienced individual specifically designed to nurture both professional and personal growth.…”
Section: Introductionmentioning
confidence: 99%
“…A observação desses itens pode auxiliar na criação de um programa adequado (RIBEIRO et al, 2013). (FALLATAH et al, 2018).…”
Section: Revisão Da Literaturaunclassified